Peran Pembiayaan Murabahah Dalam Pengembangan Kinerja Usaha Mikro Pada Baitul Maal Wat Tamwil (BMT) UB Amanah Syariah Laut Dendang - Elyana, Suherti Nur; Sihotang, Mutiah Khaira (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2024)
This research was conducted with the aim of finding out about the procedures for distributing murabahah financing and the role of murabahah financing in developing the performance of micro businesses at BMT UB Amanah Syariah. The method used in this research is a qualitative method with a descriptive approach, the data source in this research comes from primary data obtained from interviews with employees and customers of the BMT UB Amanah Syariah Micro Enterprise. The results of this research are that after conducting interviews, prospective customers can receive Murabahah financing if the criteria comply with established rules and can complete all Murabahah financing distribution procedures such as filling out financing applications, checking administrative completeness, carrying out surveys, financing decisions, signing financing agreements. , disbursement of funds to guarantee financing. If the criteria and procedures have been fulfilled by the prospective customer, the customer will get the desired loan. If customers want to open a micro business, BMT UB Amanah Syariah will guide and develop micro business customers, especially businesses that are just starting out.